Biosimilars: State of Clinical and Regulatory Science - Agnes Victoria Klein; Jian Wang; Brian G. Feagan; Mark Omoto (Frontiers Media S.A., 2018)
On May 12, 2017, various issues and challenges associated with biologics were discussed during a session of the annual joint conference of Canadian Society for Pharmaceutical Sciences and Canadian Chapter of Controlled Release Society at Hyatt Regency Hotel, Montréal, QC, Canada.  An update on the Canadian regulatory guidelines for biosimilars was given, followed by viewpoints expressed by regulatory, academic and industry scientists.  Topics of discussion included: reference biologic drug, clinical considerations, immunogenicity, extrapolation and clarification of terminology, product monograph, international collaboration, switching and interchangeability, naming conventions, clinical and non-clinical evaluation, authorization of indications, statistical equivalence, the nor-switch study and biologics marketplace.